Access arrangements for secondary students. Are they fit for purpose?. Issue 2 (13th July 2022) - McGhee, Emily; Masterson, Jackie
Abstract : The purpose of this study was to investigate Access Arrangements (AA) which allow students with specific learning difficulties (SpLDs), disabilities or medical needs to access assessments by making reasonable adjustments, as established by the Equality Act 2010. A review of the literature revealed some problematic issues relating to the perceived manageability of the system, assessments used to ascertain eligibility for AAs, the evidence‐base for specific AAs, some training routes to become an assessor, and the lack of stakeholder voice in the process. The present study involved gathering information on views and experiences with AA by means of a survey with 513 UK educational professionals, in‐depth interviews and a small‐scale study involving pupils with reading difficulties. The results suggest that the system needs reviewing to make sure there is equitable provision for all those who need AA.